Online multimodal rehabilitation programme to improve symptoms and quality of life for adults diagnosed with long COVID-19: a Randomised Clinical Trial protocol - León-Herrera, Sandra; Magallón-Botaya, Rosa; Oliván-Blázquez, Bárbara; Sagarra-Romero, Lucía; Jaurrieta, Carlos Martín; Méndez-López, Fátima (Frontiers in Public Health, 2023)
Background: Long COVID is a multisystemic condition which affects quality of life and implies a multidisciplinary treatment approach. There is still limited evidence on management techniques for this syndrome. "Telerehabilitation" could be an important tool when addressing the symptoms of this patients with the aim of increasing their quality of life. The purpose of this trial is to analyse the effectiveness of an online multimodal rehabilitation programme to improve the symptomatology of people with long COVID and their quality of life.Methods: A pragmatic randomised controlled trial will be performed with two parallel groups: (1) usual treatment by the primary care practitioner (Treatment as usual, TAU; control group) and (2) TAU plus the use of an online multimodal rehabilitation programme, including videoconferences and content published on a Moodle platform (intervention group). The data will be collected before and after the intervention. A follow-up will take place 3 months later.Discussion: There is still a lack of knowledge regarding the management of the symptoms of long COVID. This creates the need to add scientific evidence on the care of this disease, considering that multidisciplinary social and health teams can offer the necessary care so that these patients can recover their previous quality of life.The protocol for this study was registered with the ISRCTN Registry (registration number: ISRCTN15414370) on